Reconstruction of Al-Qur'an-Based Moral Education: A Thematic Study of Maqasid Al-Qur'an in Integrating Moral Knowing, Feeling, and Action Towards Indonesia Emas 2045 - Matsaini Matsaini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The phenomenon of moral degradation and disconnection between ethical knowledge and social behavior is a crucial obstacle to Indonesia's vision 2045. This gap often manifests itself in "moral paralysis" in which individuals fail to convert knowledge into ethical action. This research aims to reconstruct the paradigm of Qur'an-based moral education through the integration of the dimensions of moral knowing, feeling, and action in the perspective of Maqasid Al-Qur'an. Using a qualitative-descriptive method with a thematic interpretation approach (maudhu'i) and asrar al-tasyri' analysis, this study synthesizes Thomas Lickona's character trilogy with Islamic transcendental values. The results of the study formulated three character pillar transformations: 1) The pillar of knowing through tafakkur and tadabbur to form Al-Furqan's ability to ward off cognitive distortion (deceived by cleverness); 2) The pillar of feeling through tazkiyatun nafs as a mechanism of mental resilience in managing moral injury) to achieve inner integrity (qolbun salim); and 3) The pillar of action through the habit of charity to overcome the phenomenon of "reluctant compliance" towards sedentary autonomous actions (malakah). The novelty of this research lies in the use of Maqasid Al Qur'an as an integrative framework that bridges modern moral psychology with the goal of sharia to maintain the benefit of reason (hifz al-'aql), soul (hifz al-nafs), and religion (hifz al din). This conceptual model offers a strategic foundation for educators to build a character education ecosystem that is adaptive to the disruptions of the times in order to produce human resources with integrity to welcome the Golden Indonesia 2045.